Identification and Functional Characterization of a Putative Alternative Oxidase (Aox) in Sporisorium reilianum f. sp. zeae - Hector Mendoza; Caroline D. Culver; Emma A. Lamb; Luke A. Schroeder; Sunita Khanal; Christian Müller; Jan Schirawski; Michael H. Perlin (Journal of Fungi, 2022)
The mitochondrial electron transport chain consists of the classical protein complexes (I–IV) that facilitate the flow of electrons and coupled oxidative phosphorylation to produce metabolic energy. The canonical route of electron transport may diverge by the presence of alternative components to the electron transport chain. The following study comprises the bioinformatic identification and functional characterization of a putative alternative oxidase in the smut fungus Sporisorium reilianum f. sp. zeae. This alternative respiratory component has been previously identified in other eukaryotes and is essential for alternative respiration as a response to environmental and chemical stressors, as well as for developmental transitionaoxs during the life cycle of an organism. A growth inhibition assay, using specific mitochondrial inhibitors, functionally confirmed the presence of an antimycin-resistant/salicylhydroxamic acid (SHAM)-sensitive alternative oxidase in the respirasome of S. reilianum. Gene disruption experiments revealed that this enzyme is involved in the pathogenic stage of the fungus, with its absence effectively reducing overall disease incidence in infected maize plants. Furthermore, gene expression analysis revealed that alternative oxidase plays a prominent role in the teliospore developmental stage, in agreement with favoring alternative respiration during quiescent stages of an organism’s life cycle.